Synthesis and structure of two platinum(II) complexes containing methyl eugenoxyacetate and 2-aminobenzothiazoles - Thanh Chi, Nguyen Thi; Hoa, Nguyen Thi (Vietnam Journal of Chemistry, 2016)
Two organometallic complexes of Pt(II), trans-[PtCl2(Meteug)(Bzt)] (M1) and trans-[PtCl2(Meteug)(6-MeOBzt)] (M2) (Meteug: methyl eugenoxyacetate, Bzt: 2-aminobenzothiazole, MeOBzt: 2-amino-6-methoxybenzothiazole), have been synthesized for the first time. The structures of M1 and M2 were determined by analysis of Pt and water of hydration proportion, IR, 1H NMR and 13C NMR spectra. Meteug coordinates with Pt(II) through C=C of the allyl group in both compounds, Bzt and MeOBzt coordinate with Pt(II) via N heteroatom and at trans position compared to the allyl group.